NADPH Oxidase: A Potential Therapeutic Target to Reduce Primary Sclerosis Cholangitis Following Liver Transplantation - Aliakbarian, Mohsen; Ashrafzadeh, Kiarash; Ferns, Gordon A; Hadian, Reyhaneh; Khodashahi, Rozita; Arjmand, Mohammad-Hassan (Current medicinal chemistry, 2025)
The molecular mechanisms and causes of primary sclerosis cholangitis (PSC) post-liver transplantation are still unclear. PSC is a progressive cholestatic hepatobiliary disease that happens in about 25% of patients post-liver transplantation and requires re-- transplantation. Nicotinamide adenine dinucleotide phosphate oxidase (NADPH oxidase or Nox) is a family of transmembrane proteins whose main function is producing reactive oxygen species (ROS). ROS generation as a result of NADPH oxidase activity of Kupffer cells and polymorphonuclear leukocytes has been implicated in the pathogenesis of ischemia-reperfusion injuries after liver transplantation, and is related to intraand/ or extrahepatic non-anastomotic biliary stenosis or PSC. In addition, Nox-derived ROS upregulates several molecular pathways to induce hepatocyte apoptosis and hepatic stellate cell (HSC) activation to promote hepatobiliary fibrogenesis. Understanding the multiple molecular aspects of Nox in the development of PSC post-transplantation may help identify new drugs to prevent this disorder.